2016
DOI: 10.4025/cienccuidsaude.v15i3.31787
|View full text |Cite
|
Sign up to set email alerts
|

<b>Práticas de autocuidado no primeiro ano pós-parto/ Self-care practices in the first year postpartum<b>

Abstract: O puerpério é um período complexo, vivido e percebido de forma singular pela mulher, no qual a assistência profissional deve ser pautada no cuidado integral, fundamentado em seu contexto sociocultural. O objetivo deste estudo foi avaliar possíveis associações da 'prática do autocuidado' referida pela mulher com indicadores sociodemográficos e com as exigências propostas na Teoria de Orem (universais, de desenvolvimento e de desvio de saúde), no primeiro ano pós-parto. Trata-se de um estudo transversal, aninhad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A study warns that, since the woman starts to center the focus on the NB, she often forgetting about self-care, and problems and complications become common in this period. 29 In order to capture the puerperal woman early, the authors suggested the importance of scheduling the puerperal consultation on the same day as the foot test collection 30,31 or at the time of the BCG vaccination 31 to provide opportunities for the return of the binomial. It is emphasized that the BCG vaccine, despite regional variations, has national coverage above 90%, 32 an index equivalent to the results found in this study.…”
Section: Coefficientmentioning
confidence: 99%
“…A study warns that, since the woman starts to center the focus on the NB, she often forgetting about self-care, and problems and complications become common in this period. 29 In order to capture the puerperal woman early, the authors suggested the importance of scheduling the puerperal consultation on the same day as the foot test collection 30,31 or at the time of the BCG vaccination 31 to provide opportunities for the return of the binomial. It is emphasized that the BCG vaccine, despite regional variations, has national coverage above 90%, 32 an index equivalent to the results found in this study.…”
Section: Coefficientmentioning
confidence: 99%